Latin squares and their applications - Keedwell, A. D.; q (Amsterdam : Elsevier, 2015)
Latin Squares and Their Applications Second edition offers a long-awaited update and reissue of this seminal account of the subject. The revision retains foundational, original material from the frequently-cited 1974 volume but is completely updated throughout. As with the earlier version, the author hopes to take the reader 'from the beginnings of the subject to the frontiers of research'. By omitting a few topics which are no longer of current interest, the book expands upon active and emerging areas. Also, the present state of knowledge regarding the 73 then-unsolved problems given at the.
7.2 The Automorphism Method of H.B. Mann7.3 The Construction of Pairs of Orthogonal Latin Squares of Order Ten; 7.4 The Column Method; 7.5 The Diagonal Method; 7.6 Left Neofields and Orthomorphisms of Groups; Chapter 8: Connections with Geometry and Graph Theory; 8.1 Quasigroups and 3-Nets; 8.2 Orthogonal Latin Squares, k-Nets and Introduction of Co-ordinates; 8.3 Latin Squares and Graphs; Chapter 9: Latin Squares with Particular Properties; 9.1 Bachelor Squares; 9.2 Homogeneous Latin Squares; 9.3 Diagonally Cyclic Latin Squares and Parker Squares.
Includes bibliographical references and index.
Online resource; title from PDF title page (ScienceDirect, viewed August 6, 2015).
Keywords: Magic squares; MATHEMATICS -- General; Magic squares; Electronic books; Electronic books; Electronic books